Potentiality of Dracaena Trifasciata Fibers as a Sustainable Raw Material for Paper Bag Production (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study evaluates the feasibility of Dracaena trifasciata (snake plant) fibers as an alternative raw material for eco-friendly paper bag production. A descriptive–experimental design was employed to compare fabricated paper bags with commercial counterparts in terms of biodegradability, water absorption, tensile strength, and dimensional properties. Results indicate that snake plant-based paper bags exhibit faster biodegradation (5 days) than commercial paper bags (7 days), while maintaining comparable water absorption. Notably, tensile strength was significantly higher for the experimental group (M = 2.55) than the commercial group (M = 1.25), with statistical significance (p < 0.05) and a very large effect size. These findings suggest that D. trifasciata fibers are a viable, sustainable, and high-performance alternative for packaging applications. The study contributes to the advancement of non-wood fiber utilization in sustainable materials science.